Penggunaan Metode Tanya Jawab Dalam Meningkatkan Efektivitas Pembelajaran Mata Kuliah Microteaching Mahasiswa Universitas Sunan Giri Surabaya - Hilmi Muzayyin; Anasro; Muhammad Yusron Maulana El-Yunusi (Impressive: Journal of Education, 2024)
Learning methods are approaches or strategies used by teachers to deliver subject matter to students. The question and answer method encouraged students to be directly involved, appear brave, and confident when giving answers. The purpose of this study was to determine the ability of UNSURI graduate students in providing teaching about Islamic Religious Education material to UNSURI undergraduate students. This research uses a qualitative approach. Data collection techniques were conducted through interviews, observations, and documentation studies. Researchers conducted a process of collecting, reducing, and concluding data, then testing the validity of the data through triangulation techniques. The results showed that to improve effective learning, the right strategy is needed so that learning can run optimally and effectively. The use of question and answer methods used by graduate students greatly affects the effectiveness of learning. Interactions carried out by postgraduate students and undergraduate students in learning can stimulate the cognitive, affective and psychomotor abilities of undergraduate students.